2020
DOI: 10.1103/physrevlett.125.097201
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Mechanism for Anisotropic Magnetoresistance and Experimental Confirmation in CoxFe1x Single-Crystal Films

Abstract: Using first-principles transport calculations, we predict that the anisotropic magnetoresistance (AMR) of single-crystal Co x Fe 1−x alloys is strongly dependent on the current orientation and alloy concentration. An intrinsic mechanism for AMR is found to arise from the band crossing due to magnetization-dependent symmetry protection. These special k points can be shifted towards or away from the Fermi energy by varying the alloy composition and hence the exchange splitting, thus allowing AMR tunability. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 51 publications
7
28
0
Order By: Relevance
“…The existence of the intrinsic contribution has also been investigated experimentally. Hupfauer et al demonstrated the crystalline AMR effect, originating from the difference in electronic density, through its magnetization orientation 19 , and Zeng et al reported the intrinsic contribution caused by the magnetization-direction-dependent band crossing effect 20 .…”
Section: Introductionmentioning
confidence: 99%
“…The existence of the intrinsic contribution has also been investigated experimentally. Hupfauer et al demonstrated the crystalline AMR effect, originating from the difference in electronic density, through its magnetization orientation 19 , and Zeng et al reported the intrinsic contribution caused by the magnetization-direction-dependent band crossing effect 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Zeng et al [3] used a sophisticated first-principles code designed to calculate the transport properties in the presence of impurities, spin-orbit interaction, as well as magnetic, thermal and alloy disorder [7]. The excellent agreement of the calculated results with the AMR measured at Fudan and Argonne supports the validity of the method.…”
mentioning
confidence: 99%
“…Alloys of the transition metals Fe, Ni, and Co are the materials of choice because they combine a large AMR ratio with other convenient properties [2]. In a convergence and culmination of methods and ideas developed in the past decades, a collaboration led by Zhe Yuan from Beijing Normal University (theory) and Yizheng Wu from Fudan University (experiments) recently solved the conundrum of the AMR for the generic alloy Co x Fe 1−x [3].…”
mentioning
confidence: 99%
See 2 more Smart Citations